Communication Patterns Of Parents' Closeness With Students In La Tansa Boarding School - Agustina, Alya; Supratman, Lucy Pujasari (eProceedings of Management, 2024)
Islamic boarding schools are Islamic educational institutions that have become a symbol of Islamic education inIndonesia.Pondok pesantren are present not only as an educational alternative to public school academies, but havealso become the main choice for parents who want to entrust their children to study Islam better and more deeply(Syahrani, 2022).This requires parents and students to live separately and far apart due to boarding school regulationsthat require students to live in dormitories and not be allowed to bring communication media tools to the dormitory;asa result, parents cannot contact them in advance and students have to attend school and live a life with dormitoryregulations that keep students quite busy.In general,it is difficult for parents and students to connect in person orthrough communication media. The purpose of this study is to find out how the communication patterns of parentsand children who are in boarding school maintain their close relationship.The research method used in this study isqualitative, with a case study approach.The findings of this study are that there are three families who use democraticcommunication patterns, one family uses permissive communication patterns and one family uses authoritariancommunication patterns. Keywords-boarding school, family communication patterns, parents and children